Light Shelf as a Daylighting System in a Tropical Climate Office Space - ., Abimaje; ., Joshua; Zin Bin Kandar, Mohd; Yakubu Aminu, Dodo (International Journal of Engineering and Technology, 2018)
Daylighting is a passive design strategy for lighting office spaces given the fact that offices operate within daytime, usually between 8:00 am to 5:00 pm which corresponds to the period of daylight availability.Â Daylight is abundant in the tropics, free and has no negative impact on the environment.Â It has positive physiological and psychological effect on the man as well as good colour rendering.Â Ironically, despite the abundant availability and the merits of daylighting especially in the tropics, it is not fully utilized.Â A light shelf is one of the innovative daylighting systems that can be employed to improve office spaces daylighting performance.Â Therefore, the focus of this study is the application of light shelf as a daylighting system in government offices in Malaysia.Â This study was carried out through literature search on thirteen disciplines.Â The disciplines were building and environment, energy, and building, renewable and sustainable energy, energy conservation in Building, lighting research and technology, energy conservation and Management, Solar energy, renewable energy, indoor and built environment, energy policy, energy and buildings, renewable energy, and applied energy.Â Data were obtained from Science Direct, Web of Science, Scopus and Conference Proceedings.Â This was done by typing in keywords such as daylighting, light shelf, office spaces, visual performance, tropical climate, and Malaysia.Â The review was from 1986 to 2016 to cover the length and breadth of the study area for the past 30 years.Â This work includes previous review and empirical works.Â Attention was equally given to the methodologies and context of the work.Â The result of this study showed the poor daylighting performance of government office spaces in Malaysia.Â The daylighting in these offices is either too low as a result of the use of excessive external shading devices to reduce interior heat gain or too high due to over glazed wall for aesthetics and daylighting.Â Consequent upon these is inadequate daylighting illuminance, non-uniform illuminance distribution, and glare.Â This brings about visual discomfort.Â Also, the study revealed that light shelf as an innovative daylighting lighting system could improve the daylighting performance of these office spaces.Â The effectiveness of light shelf depends on the latitude, reflectance of light shelf material, the angle of inclination, its depth, mounting position among others.Â However, there exists little work on the effect of the depth of light shelf and the variation of its distance from the ceiling on the daylight performance of government office spaces in Malaysia.Â This paper, therefore, recommends investigation on the effect of the depth of light shelf and the variation of its distance from the ceiling on daylighting performance of government office spaces in Malaysia.Â Â